Pengelompokan Performansi Rasio Keuangan Perusahaan Terafiliasi dengan Israel Pasca 07 Oktober 2023 menggunakan AHC Clustering - Mahardika Lutvia Maharaja; Tora Fahrudin; Rochmawati Rochmawati (Politeknik Ganesha Medan, 2025)
The economy and financial performance of companies can be affected by geopolitical conflicts, especially companies that have ties with countries involved in the conflict. The purpose of this research is to cluster the financial ratios of companies affiliated with Israel after October 7, 2023, using the AHC (Agglomerative Hierarchical Clustering) method. The analysis was conducted based on key financial ratios, namely ROA (Return on Assets), ROE (Return on Equity), DER (Debt to Equity Ratio), Net Profit Margin (NPM), and CR (Current Ratio). The clustering results show that the businesses are divided into three main clusters. The first cluster consists of companies with high profitability but low liquidity, indicating an aggressive financial strategy that takes on greater liquidity risk. Companies in the second cluster show good financial stability because they have balanced liquidity and profitability. Companies in the third cluster have high liquidity but low profitability, indicating a more conservative financial approach. This result allows the company to gain an overview of the financial performance within the company after the occurrence of the Israel-Palestine conflict. This study helps investors, regulators, and the company itself understand how geopolitical instability affects financial performance. Additionally, the research findings can serve as a basis for strategic decisions related to risk mitigation and optimization of financial performance in an uncertain global economic environment.